Stimulating Managerial Capital in Emerging Markets : The Impact of Business Training for Young Entrepreneurs - Bruhn, Miriam; Zia, Bilal (Taylor and Francis, 2013)
Identifying the determinants of entrepreneurship is an important research and policy goal, especially in emerging market economies where lack of capital and supporting infrastructure often impose stringent constraints on business growth. This paper studies the impact of a comprehensive business and financial literacy programme on firm outcomes of young entrepreneurs in an emerging post-conflict economy, Bosnia and Herzegovina. The authors conduct a randomised control trial and find that, while the training programme did not influence business survival, it significantly improved business practices, investments and loan terms for surviving businesses. Female-run businesses further exhibited some improvements in business performance and sales.